Från miljöarbete till hållbar utveckling - en studie av fem företag - Grimmefält, Johanna; Josefsson, Julia (My University, 2003)
During the 90s most companies organized and adopted routines for their environmental work. This work included for example eco-efficiency improvements and the introduction of environmental managing systems. At the UN conference in Rio in 1992 the concept Sustainable development was defined, but it was not until about the year of 2000 that companies in Sweden shifted their work from environmental management to sustainable management. A consequence of this is that they now have to focus on environmental aspect in conjunction with social and economic aspects. The purpose of this study is to gain understanding of what a change of focus to sustainable development means for companies. Has the environmental work suffered in the competition with social/economical aspects under the new sustainable focus? How will the new way of working affect the balance between environmental and social aspects? Changes were studied in five companies by analysing their annual-, environmental- and sustainability reports and through interviews of sustainable managers. The information observed during the study have been analysed with respect to environmental and social aspects. The economic aspect is not considered in the study. The main purpose is to observe changes over time and not to compare companies. The companies included in the study are ABB, HM, ITT Flygt, Skanska and Sydkraft. To analyse the information gathered in the study a model have been created. Among the conclusions from the study are that the companies due to the work with sustainability try to build the image of “a responsible and caring company”. With this image the companies hope to gain market shares, make it more competitive and make savings e g through a lower staff turnover or less sick leaves. The organizations of the companies are sometimes changed due to the new way of working. The environmental department are often just given the general responsibility for the work with sustainability therefore no resources are taken from the environmental work. Environmental work varies more across industrial sectors than social work.
Keywords: Miljöteknik; Environmental engineering